The different faces of addiction: understanding a complex disorder from different perspectives (Deutscher Suchtkongress, 2023)
Addiction to drugs is an illness that causes a lot of harm to everyone involved, but the pain and damage it causes does not seem to deter users from continuing to consume drugs. Many chronic drug users report that even though they don’t enjoy taking drugs as much as they used to, they still continue doing it. Though this may seem paradoxical at first glance, such maladaptive behaviour could be explained by changes in brain regulatory control systems. The two psychological constructs, impulsivity, and compulsivity, characterise failures of regulatory control that lead to undesirable consequences. Although both constructs are hallmarks of drug addiction, they are not specific to addiction, but there is now growing evidence suggesting that both may facilitate the development of addiction and exacerbate its course.  In my talk, I will tackle questions frequently brought up in this context, for example why it is that some people get addicted to drugs and others don’t. Or why it is so particularly difficult to change behaviour in people who are addicted to drugs. Furthermore, I will highlight some of the less well-known effects of stimulant drugs, which may also contribute to the persistence of stimulant drug addiction. Cognitive neuroscience is a powerful tool to not only understand the causes of behaviour spiralling out of control, but also to identify pathways for getting it back under control. Ultimately, science provides a real opportunity to make a difference to the lives of people affected by debilitating disorders such as drug addiction.